(untitled) (International relations and international law Journal, 2020)
This research paper investigates a broad understanding of the concept of protecting the rights of Minorities and Indigenous peoples as one of the development practices in international law. In particular, the research will deal with the protection and rights of Indigenous peoples which is already enshrined in the United Nations Declaration on the Rights of Indigenous Peoples. Consequently, it is regarded to be a legal document of these communities in order to develop themselves and protect their rights as regards land, resources and others. The another aim of this paper is to critically discuss the issue concerning the rights of lands and property of indigenous peoples, and also according to international provision whether state can launch economic project on the territory of indigenous peoples without their consent. Further, the study showed that the UN international instruments also helped for the protection of indigenous people and minority rights. However, still the international order needs certain enhancement in the international covenants and international organizations role in this regard is very crucial. Key words: minorities, Indigenous peoples, international law, self-determination, consent, declaration, provision.